Accuracy of Calf Circumference Measurement, SARC-F Questionnaire, and Ishii's Score for Screening Stroke-Related Sarcopenia - Yao, Ruihong; Yao, Liqing; Yuan, Changli; Gao, Bu-Lang (Frontiers in Neurology, 2022)
Objective The purpose of this study was to investigate the accuracy of sarcopenia diagnosis in patients with stroke using calf circumference (CC), SARC-F questionnaire, and Ishii's score in comparison with the Asian Working Group for Sarcopenia 2019 (AWGS) sarcopenia diagnostic criteria. Materials and Methods In this cross-sectional study, a total of 364 consecutive patients with stroke were enrolled and evaluated with the CC measurement, SARC-F questionnaire, and Ishii's score. The diagnostic accuracy was analyzed. Results Based on the AWGS criteria, sarcopenia was present in 180 (49.5%) patients, with an age range of 49–74 (mean 63 ± 14.7) years. In all patients, the cutoff value of CC in the accuracy of diagnosing sarcopenia was 30.5 cm, with an AUC of 0.85, sensitivity of 81.8%, specificity of 90.1%, Kappa value of 0.72, and Youden index of 0.72. In the accuracy of diagnosing sarcopenia in all patients, Ishii's score had a cutoff value of 118, AUC of 0.78, sensitivity of 90.1%, specificity of 36.0%, Kappa value of 0.4, and Youden index of 0.55. For accuracy of diagnosing sarcopenia, the SARC-F questionnaire had a cutoff value of 5, AUC of 0.731, sensitivity of 94.7%, specificity of 40%, Kappa value of 0.34, and Youden index of 0.41. Conclusions Based on the AWGS criteria, calf circumference measurement has the optimal performance in screening stroke-related sarcopenia compared with the SARC-F questionnaire and Ishii's score. In patients with stroke, the cutoff value of calf circumference for sarcopenia is < 31 cm in men and 30 cm in women, and with an AUC of 0.85.